Looking for Blame: Rape Myth Acceptance and Attention to Victim and Perpetrator. Issue 15 (August 2017) - Süssenbach, Philipp; Eyssel, Friederike; Rees, Jonas; Bohner, Gerd
In two studies, the authors examined the influence of rape myth acceptance (RMA) on participants' attention toward the potential victim versus perpetrator in a rape case. In Study 1 ( N = 90), participants selected information that focused on either the male defendant or the female victim. With increasing RMA, participants preferred information that focused on the victim rather than the defendant. In Study 2 ( N = 41), participants viewed photographs depicting both victim and defendant while their eye movements were recorded. With increasing RMA, participants spent less time inspecting the defendant relative to the victim. In both studies, higher RMA predicted stronger anti-victim and pro-defendant judgments, replicating previous research. Taken together, these results support the assumption that RMA guides participants' attention, leading to a focus on the alleged rape victim and away from the alleged perpetrator. Implications of the current research and future directions are discussed.